Validitas Media Pembelajaran Interaktif Berbasis Inkuiri Terbimbing untuk Meningkatkan Keterampilan Proses Sains - Krestina Kusumawati; Iin Murtini (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to determine the validity of guided inquiry-based interactive learning media in improving students' Science Process Skills (SPS). The research used a research and development (R&D) approach with a 4D development model, encompassing the stages of definition, design, development, and dissemination, but limited to the development stage. Data were collected using a validation sheet covering aspects of content/material, systematics, language, graphics, and science process skills. This was conducted by expert validators, namely two lecturers from the Department of Biology Education. Data analysis was conducted using quantitative descriptive analysis techniques using validity formulas and criteria for interpreting product validity scores. The results showed that the overall average validation test result for the interactive learning media obtained a score of 89%, indicating a very valid category. Therefore, the validity of the guided inquiry-based interactive learning media has reached product validity and can be developed into the dissemination stage.